(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This scientific article explores the philosophical understanding of time and space in the teachings of Ibn Sina. Linking time with the concepts of space and movement, Ibn Sina argues that time does not exist without movement. He presents arguments that support the objective nature of time. His view of space is also discussed, where he rejects the idea of emptiness and argues that space is the boundary of the surrounding body, filled with a moving body. The article emphasizes the philosophical significance of time and space in the teachings of Ibn Sina and their correspondence to modern physical concepts.